Hamiltonian hierarchy of pseudo-potentials - dos Anjos, Rita de Cassia [UNESP]; Drigo Filho, Elso [UNESP]; Ricotta, Regina Maria [UNESP] (Iop Publishing Ltd, 2007)
The general structure of the Hamiltonian hierarchy of the pseudo-Coulomb and pseudo-Harmonic potentials is constructed by the factorization method within the supersymmetric quantum mechanics (SQMS) formalism. The excited states and spectra of eigenfunctions of the potentials are obtained through the generation of the members of the hierarchy. It is shown that the extra centrifugal term added to the Coulomb and Harmonic potentials maintain their exact solvability.